The antiquity of the Italian nation the cultural origins of a political myth in Modern Italy, 1796 - 1943 - De Francesco, Antonino 1954- (Classical presences, 2013)
With Italy under Napoleonic rule at the beginning of the nineteenth century, the antiquarian topic of anti-romanism became a pillar of the Italian nation-building process and, in turn, was used against the dominant French culture. The history of the Italian nation predating the Roman Empire supported the idea of an Italian cultural primacy and proved crucial in the creation of modern Italian nationalism. Towards the end of the nineteenth century, Italian studies of Roman history would drape a dark veil over the earliest history of Italy while Fascism openly claimed the legacy of the Roman Empire. Italic antiquity would, however, remain alive through all those years, intersecting with the political and cultural life of modern Italy